Systematic analysis of the biological roles and pharmacological properties of D-chiro-inositol - Olga A. Gromova; Ivan Yu. Torshin; Elena V. Uvarova; Natalya I. Tapilskaya; Alla G. Kalacheva (IP Berlin A.V., 2020)
D-chiroinositol (DCI) is one of the 9 inositol isomers that forms inositol phosphoglycans, which are mediators of the action of insulin. The metabolism of DCI and myo-inositol (MI) is impaired against the background of insulin resistance, including the patients with polycystic ovary syndrome (PCOS). Aim. Highlight the most characteristic pharmacological properties of DCI. Materials and methods. Systematic computer analysis of 45 600 publications on the biological roles of inositol by methods of the topological theory of pattern recognition and systems biology analysis of human proteome. Results. A complex of interactions between metabolic disorders of DCI, PCOS, ovulation disorders, obesity associated with numerous hormonal disorders is described. Supplements with DCI and MI increase the sensitivity of cells to insulin and normalize the metabolism of androgens. An important difference between DCI and MI is the presence of DCI in the composition of inositol phosphoglycans that mediate the action of insulin on cells, as well as its participation in the realization of the therapeutic effects of metformin. The use of the MI+DCI combination allows achieving positive dynamics in reducing excess body weight, normalizing blood lipids, glucose and insulin levels, restoring the ovulatory menstrual cycle, improving oocyte quality, and helps prevent gestational diabetes in pregnant women and macrosomia of the fetus. DCI is more effective than MI in reducing the risk of folate-resistant neural tube defects. Conclusion. The therapeutic potential of DCI in combination with MI for treating PCOS and hyperandrogenism is evident. Depending on the therapeutic expediency, various ratios of MI:DCI can be used for the treatment of PCOS and disorders of carbohydrate and lipid metabolism.A